FIFA World Cup and corruption: an analysis by the Synthetic Control Method applied to the host countries from 2006 to 2014 - Da Costa Silva, Pedro Henrique; Pereira Coimbra, Leandro Willer; Soares Monteiro, Valdeir (Espacio Abierto, 2023)
The exogenous impact on public expenditures and the short time frame for their execution, represented by investments and other expenses, required to host the FIFA World Cup, create a scenario more propitious for corrupt practices that are not properly monitored by society due to the enthusiasm generated by the preparations for the event. The objective of this study is to evaluate the effect of preparation for and realization of the World Cup in the host countries on the public perception of corruption in those countries. For this purpose, we employ the synthetic control method as described by Abadie, Diamond and Hainmueller (2010), who utilized the announcement of the host country as a shock to the Corruption Perception Index formulated by Transparency International. The host countries analyzed are Germany (2006), South Africa (2010) and Brazil (2014). The announcement of the host country was related to an increase in the perception of corruption in the countries analyzed, but this effect tended to wane as the event approached. The lower corruption perception evidenced by the method does not jibe with the scenario of corruption scandals that emerged after the event, mainly in South Africa and Brazil.